PERANCANGAN SISTEM KERJA BERBASIS SOP: SOP-BASED WORK SYSTEM DESIGN - Mulyadi (Engineering and Technology International Journal, 2020)
The purpose of this research is to design a work system based on Standard Operating Procedures (SOP) for processing export and import documents. The data collection method used is the literature study method, the observation method and the interview method. The result of this research is the design of a work system based on Standard Operating Procedures (SOP).